The Impact of the Technology Used in Formative Assessment: The Case of Spelling. (January 2017) - Vásquez, Andrea; Nussbaum, Miguel; Sciarresi, Enzo; Martínez, Tomás; Barahona, Camila; Strasser, Katherine
This study demonstrates how the technology used to assist formative assessment in spelling can have an impact on learning. Formative assessment represents a set of student-centered practices, the results of which are not always optimal. Furthermore, different technologies are better suited to certain tasks than to others. The study follows a Design-Based Research approach and was conducted in Chile in two phases. In the first phase of the study, a formative assessment strategy for teaching spelling is developed. In a subsequent phase, the impact of different technologies on this strategy is analyzed. This is achieved by comparing two different technologies: Tablet PCs and the interpersonal computer. The results reveal that a self-paced formative assessment strategy using Tablets is more effective than the same strategy using an interpersonal computer when teaching spelling to primary school students. This therefore highlights the impact of technology on learning when adopting a formative assessment strategy.